Giant symptomatic serous cystadenoma mimicking carcinoma: A case report and literature review. (2019) - Pointer, Lauren; Rothermel, Luke D.; Strosberg, Carolina; Anaya, Daniel; Hodul, Pamela
Highlights: The diagnosis of serous cystadenoma is challenging. Surgery may be indicated for select serous cystadenoma. Serous cystadenocarcinoma is a rare entity and histologically indistinguishable from its benign counterpart. Abstract: Introduction: Advanced imaging has led to an increase in the incidental diagnosis of pancreatic cysts. Serous cystadenomas (SCAs) account for nearly 30% of cases. These are typically considered benign lesions but up to 16% of cases are resected for aggressive behavior and symptoms. Presentation of case: A 64 year old female presented with a large incidental cyst in the pancreatic body. Pre-operative imaging conferred a diagnosis of SCA. After 2 years the cyst grew resulting in abdominal pain. Enlargement was associated with splenic vein occlusion and varices of the short gastric vessels. This change in behavior was concerning for malignant transformation. The cyst was resected by distal pancreatectomy and splenectomy. The patient recovered with minimal morbidity. Final pathology revealed a 15.5 × 10.3 × 8.5 cm SCA with negative margins. Discussion: In this case a patient presents with aggressive radiographic features and new symptoms suggesting malignant transformation of a previously diagnosed SCA on imaging. Although malignant variants can be diagnosed by findings of metastatic deposits at the time of surgery or as recurrence years later, histologic findings cannot discriminate benign from malignant potential. Preoperative imaging is challenging with erroneous characterization in nearly 60% of cases. Conclusion: Based on the low risk of malignancy, selective surgical resection for SCA appears warranted. Accepted indications for surgery include development of symptoms or concern for correct diagnosis in a medically fit individual. Routine resection for cysts >4 cm has been suggested however, prospective studies are needed to determine benefit over risk rationale.